(untitled) (Fiep Bulletin - online, 2012)
Quality of life is a holistic concept, related to current and past experiences of the person. The term bullying can be completely operated through an instrument, as there is reasonable doubt about its "best" definition. Requiring the intervention of adults, bullying includes various forms of aggression, being both intentional and repetitive, with or without any apparent reason. These attacks happen in school with one or more students against another, and are understood to cause trauma because of the unequal relationship between them. This practice of prejudice of class and race offends human dignity, and brings irreparable consequences to the school life of a child, causing the child to submit to anti-social behavior and learning difficulties. This type of violence manifests itself subtly in the form of jokes, nicknames, hazing, teasing and physical aggression (Lopes Neto and Saavedra, 2003; Fante, 2005). From the results found in the pilot project, from the five children studied, 60% had experienced some form of intimidation and lack of pleasure in going to school. Therefore, it is necessary to conduct research with a larger number of children for better scientific analysis, and then to take intervention measures.